2010
DOI: 10.1080/01930826.2010.489002
|View full text |Cite
|
Sign up to set email alerts
|

When Life Hands You Lemons: Overcoming Obstacles to Expand Services in an Embedded Librarian Program

Abstract: Having launched a pilot program of embedding librarians in faculty Blackboard courses, a team of university regional campus librarians reviewed their library services to faculty teaching online, off-campus, and traditional courses, and returned for Round 2. Just as the library services offered in this collaborative effort were taking off, conditions worsened. A storm of staff reductions, budget cuts, and administrative reorganization hit. Despite the climate of uncertainty and challenges, the embedded libraria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…Earlier studies evaluating the efforts of embedded librarians in online classes, and the perceptions of students in those classes, employed various combinations of online student surveys and faculty/librarian interviews (Figa, Bone, & Macpherson, 2009), online surveys of both students and faculty combined with informal discussions with librarians (Tumbleson & Burke, 2010), or online student surveys combined with discussion forum feedback and faculty interviews (Kumar et al, 2010). We chose to use a combination of online surveys and analysis of usage statistics gathered from the university's course management system (CMS).…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies evaluating the efforts of embedded librarians in online classes, and the perceptions of students in those classes, employed various combinations of online student surveys and faculty/librarian interviews (Figa, Bone, & Macpherson, 2009), online surveys of both students and faculty combined with informal discussions with librarians (Tumbleson & Burke, 2010), or online student surveys combined with discussion forum feedback and faculty interviews (Kumar et al, 2010). We chose to use a combination of online surveys and analysis of usage statistics gathered from the university's course management system (CMS).…”
Section: Methodsmentioning
confidence: 99%
“…Using an embedded librarian approach in professional development courses for faculty is one way by which to market library services to distance faculty and gain visibility across campus. Examples of faculty-librarian collaborations abound in the literature for face-to-face classes, and, increasingly, the concept of embedded or blended librarians have shaped how services are offered to online and distance students (Bell & Shank, 2007;Courtney & Wilhoite-Mathews, 2015;Landry-Hyde & Cantwell, 2013;Mune et al, 2015;Tumbleson & Burke, 2010;Easter et al, 2014). Still, marketing these services to faculty, and also teaching faculty how they can be implemented for a virtual classroom setting, can be a challenge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is room for more embeddedness, although it is a challenge for one person to be everywhere, and the literature has indicated that "going it alone" is not the best approach (Tumbleson & Burke, 2010;York & Vance, 2008). The single person "super liaison" model we use to support all of the SPS departments has been beneficial in developing a physical sense of support, although there are limitations to working alone (Jaguszewski & Williams, 2013).…”
Section: Further Researchmentioning
confidence: 99%